Prenatal diagnosis of anomalous connection of the inferior caval vein to the left atrium associated with common arterial trunk. Issue 5 (20th December 2020) - Houyel, Lucile; Cohen, Laurence; Burlot, Patrick; Heitzmann, Anne; Bonnet, Damien
Abstract: Anomalous connection of the inferior caval vein to the left atrium is exceedingly rare, and has even been considered by some authors an anatomic and embryologic impossibility. This study demonstrates for the first time the existence of this rare malformation, diagnosed on prenatal echo, and confirmed on post‐mortem examination in a 24 WG fetus, in association with a common arterial trunk. Abstract : Fetal echocardiography, subcostal coronal view. The superior caval vein (SCV) is connected to the right atrium (RA), the inferior caval vein (ICV) is connected to the left atrium (LA). The oval foramen is shunting left to right.